Asian Regionalism and Its Effects on Trade in the 1980s and 1990s - Ramon Clarete; Christopher M. Edmonds; Jessica Seddon Wallack (Asian Development Bank (ADB), 2002)
This brief explores the Asian Development Bank's technical assistance for expan"This paper begins by outlining the major preferential trade agreements (PTAs) in Asia and other regions and reviewing trends in trade flows. The paper uses a gravity model augmented with several sets of dummy variables to estimate the effect of various PTAs on trade flows within and across membership groupings as well as the effect of PTAs on members' trade with Asian countries. On the basis of these estimates, we are able to categorize 11 major PTAs into those that increase intrabloc trade at the expense of their respective imports from the rest of the world; those that expand their respective trade among their members without reducing their trade with nonmembers; and those that reduce trade with nonmembers without significant changes in intrabloc trade. The authors also show that PTAs have augmented trade in Asia."ding microinsurance in Mongolia and the People's Republic of China.
hdl:11540/2067
Keywords: 330; Handelspräferenzen; Internationale Wirtschaftsbeziehungen; Gravitationsmodell; Asien; Mittlerer Osten